Pemberdayaan Wanita Tani Kelompok Tani Setetes Madu Fatuleu Melalui Pelatihan Pengolahan Jagung Menjadi Jagung Marning - Musa F Banunaek (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Community empowerment is a development process in which farmers have the initiative to start the process of social interaction activities to improve their situation and condition in a better direction. To maximize farmers so that changes occur in farmers for the better, the Dry Land Agricultural Extension Study Program, Kupang State Agricultural Polytechnic conducts community service activities aimed at conducting training on processing corn into marning corn for members of the Farmer Women Group Fatuleu Honey Drops . From the results of observations, members of the Fatuleu Setetes Madu Farmer Women Farmers Group were very enthusiastic and participated in training activities both from preparatory activities, training implementation to the closing process. This community service activity provides a solution for existing farmers to be more able to develop a product business made of corn so that they can help their household economy.